Morbidity and mortality after treatment of Ewing sarcoma: A single‐institution experience. Issue 11 (18th April 2017) - Friedman, Danielle Novetsky; Chastain, Katherine; Chou, Joanne F.; Moskowitz, Chaya S.; Adsuar, Roberto; Wexler, Leonard H.; Chou, Alexander J.; DeRosa, Amelia; Candela, Joanne; Magnan, Heather; Pun, Shawn; Kahan, Tamara; et al.
Abstract: Background: Children, adolescents, and young adults treated for Ewing sarcoma (ES) are at risk for disease‐related and treatment‐related complications. We aimed to describe early and late overall mortality, cause‐specific mortality, and key adverse health outcomes in a large, single‐institutional cohort of patients with ES. Methods: Patients with ES diagnosed at age less than 40 years and treated at Memorial Sloan Kettering between 1974 and 2012 were included. Overall survival was estimated using Kaplan–Meier methods. Cox proportional hazards were used to examine the association of clinical and pathologic variables with overall survival. Cause‐specific mortality was evaluated with the cumulative incidence function accounting for competing risks. Results: Three hundred patients with ES (60.3% male; median age at diagnosis: 16.8 years [range: 0.3–39]; 30.0% with metastatic disease at diagnosis) were followed for a median of 7.8 years (range: 0.2–37). Five‐year overall survival was 65.2% (95% confidence interval [95% CI], 59.8–71.1%) for the entire cohort; 78.6% for those with localized disease; 40.1% for those with isolated pulmonary metastases; and 28.1% for those with extrapulmonary metastases. In multivariable analysis, older age at diagnosis, minority race/ethnicity, and metastatic disease at diagnosis were associated with inferior survival. Ten‐year cumulative incidence of relapse/progression was 40.1%, with eight late relapses occurring at a median of 6.3 years after diagnosis (range: 5–14). Seventeen patients developed subsequent neoplasms (treatment‐related myelodysplastic syndrome/acute myelogenous leukemia = 9; solid tumors = 6; nonmelanoma skin cancer [NMSC] = 4). Excluding NMSC and melanoma in situ, the cumulative incidence of subsequent malignant neoplasms at 25 years was 15% (95% CI, 4.8–25.1%). Conclusion: Patients with ES are at high risk for relapse/progression and second cancers.